EFEKTIVITAS RUJUKAN ONLINE BAGI PASIEN RAWAT JALAN DALAM PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) DI KOTA SOLOK - Fiqih Zetrita Putri; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to determine the effectiveness of online referrals for outpatients in the National Health Insurance Program (JKN) in the city of Solok and describe the constraints and efforts that realize the effectiveness of online referrals for outpatients in the city of Solok. This research is motivated by the obstacles in FKTP as well as complaints from participants or the community when the online referral system was implemented. This research uses a qualitative method with a descriptive approach. The instrument of data collection was through interviews, observations and documentation. The results of this study were the effectiveness of online referrals in the national health insurance program in the city of Solok. It was not effective because there were still some obstacles, both constraints from BPJS, FKTP, FKRTL and also complaints felt by the participants.